Relationship between pulmonary function tests, sputum eosinophilia and total serum IgE levels among asthmatic patients in Duhok, Iraq - Issa, Hamdia Yousif; Ramadhan, Ali A.; Safo, Abdulazeez S.; Al Habib, Omar A. M. (International Journal of Research in Medical Sciences, 2020)
Background: Bronchial asthma is a disease characterized by reversible airway obstruction, airway inflammation; and hyper-responsiveness. The prevalence of asthma is high, and both its prevalence and burden have increased over the last several decades. The study of inflammatory markers has implications for the appropriate management of this disease. Inflammatory markers has implications for the appropriate management of this disease. Objective of the study is to determine the correlation between asthma severity using pulmonary function tests with sputum eosinophilia and total serum IgE levels. Methods: This case-control study was conducted from March 2017 to September 2018 in the respiratory unit of Azadi general teaching hospital. It included 42 asthmatic patients and 18 healthy subjects. They underwent pulmonary function tests and measurement of total serum IgE levels. Induced sputum was done for asthmatic patients. Results: The age of asthmatic patients ranged from 16-70 years (mean 42±19 years). The asthmatic patient’s female: male ratio was 1.8. Mild asthma was the most common severity group (N=18, 43%) followed by moderate asthma (N=14, 33%) then severe asthma (N=10, 24%). Abnormal sputum eosinophilia (≥3%) was detected in 90% of severe asthma (N=9) compared to 36% in moderate asthma (N=5) and 5.6% in mild asthma (N=1). There was significant statistical association between asthma severity and sputum eosinophilia (p=0.00004). The association between asthma severity and total serum IgE levels was highly significant (p<0.0000) with levels of total serum IgE increasing as the severity of asthma increases. Conclusions: Severe asthma is the least common severity group in this study. Both abnormal sputum eosinophilia and total serum IgE levels are associated with the severity of asthma.